DISCRIMINATION OF RACEIN ROBERTO BENIGNI'S: LIFE IS BEAUTIFUL (1999)A MARXIST PERSPECTIVE - NUGROHO, ILHAM AKBAR (2011)
This study is aimed to show the discrimination of race in Life is Beautiful movie by using Marxist perspective. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the Marxist perspective. This research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is the Life is Beautiful movie directed by Roberto Benigni released in 1999. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each element, Roberto Benigni conveys a message that all of people want to live without oppression. It shows that the character and characterization, casting, plot, setting, point of view, theme, mise en scene, cinematography, sound, and editing are related to each other and form unity. Second, based on the Marxist perspective, there is an ethnic cleansing that makes the unbalancing and unharmonious life resulted in discrimination of race.